CRIMINAL LAW ASPECTS OF MEDICAL ERROR AND INADMISSIBLE PROVISION OF MEDICAL ASSISTANCE - CASE OF SERBIA AND SLOVENIA - Rešetar, Dejan C (Glasnik Advokatske komore Vojvodine, 2020)
Human health is forseen by criminal law as an important protective object. Although the goal in every doctors job is to improve the health and to cure the patient, sometimes there are cases of medical error. In this paper the author first discusses the definistion of the term medical error, looks at the basic division and separates the concept of medical error from similar concept such as unfortunate case and complication. A medical error will exist if a causal link is established between the doctors action and the serious impairment of the patients health of the fatal outcome. In order to avoid a medical errors, doctor is obliged to explain to the patient the posssible risks in the treatment, as weel as the risks during the surgery and postoperative course, as weel as to obtain consent from the patient. The author further discuss the specific criminal offence – Medical negligence and systhematicaly analize the criminal act in criminal law of Republic of Serbia and Republic of Slovenia. He underlines the similarity of criminal sanctions in law of Serbia and Slovenia. Further he concludes that specific criminal act is delicta propria, because the circle of persons who may be found in the role of perpetraitor is very narrow and specific.